The (In)visibility of Taiwan – Indonesia Relations: Indonesian Students on the Sideline - Rangga Aditya Elias (JAS (Journal of ASEAN Studies), 2018)
Indonesian students have been playing significant roles as the agent of change in the process of Indonesia’s nation building. In the era of Indonesia’s struggle for independent, students had become the backbone of many important movements. Students were also the driving force of Indonesia democratization movement in 1998. Thus, it can be inferred that students are the important agent in shaping the direction of Indonesia.On the other hand, discord between China and Taiwan regarding Taiwan status has been making Taiwan – Indonesia relations growth more significant in informal than formal channel. One of the efforts to increase the informal channel is undertaken by establishing academic exchanges, scholarships, and scholar exchanges. However this effort is seemingly still on creating cooperation with academic institution to increase the number of Indonesian students in Taiwan per se but it arguably could upgrade both entities relations only if the operationalization of academic policy is parallel with their  attempt to  increase  the relation.  Currently,  there are  approximately  3,052 Indonesian students enroll in many universities in Taiwan. Yet, there is no such effort applying by Taiwan government to take advantages from this situation in order to increase Indonesia-Taiwan further relations. This paper, therefore, is aimed to deliver two arguments. First, Taiwan academic relations with Indonesia are still focusing on the effort to increase the number of Indonesian students in Taiwan and neglect their potential as agent of cooperation. This condition has made the students as agent become invisible. Second, Taiwan’s policy in academic cooperation with Indonesia is not in line with Taiwan’s effort to upgrade  its relation  with  Indonesia. As  an  impact, Taiwan  –  Indonesia relation remains stagnant and invisible. In addition this paper will also deliver a clear description of the Indonesian students’ characteristic in Taiwan and the potential factors that  are  embedded on  them.  In order  to  get its  finding  and support  the secondary data, this paper also will conduct observations and interviews to the Indonesian students in Taiwan.